Applicability of current soft tissue thickness tables in forensic anthropological facial reconstruction studies in turkey (Journal of Basic and Applied Research in Biomedicine, 2022)
As rapid changes and developments are achieved in the contemporary world, the phenomenon of “crime” is also developing. In response, forensic anthropology as a part of the multi-disciplanary forensic sciences, provide precious contributions to law enforcement. One of the most important contributions forensic anthropology provides to the identification researches is the “Facial Reconstruction”. The purpose of this study is to compare Kirman (Turkish), Lebedinskaya (Russian) and Lebedinskaya (Kazakh) Soft Tissue Thickness (STT) tables versus the STTs of a test group which is derived from the Turkish population, provide contribution in increasing the accuracy of facial reconstruction practices, and test the applicability three STT tables on the Turkish population.